Community-Based Literacy Intervention Through a Sudut Baca Ceria: Increasing Children’s Interest in Reading in Rural Areas - Alfiyah, Avif; Fahimah, Siti (TAAWUN, 2026)
This community service program was conducted to enhance children’s reading interest by implementing the Sudut Baca Ceria in Brangsi Village as a model of community-based literacy empowerment. The activity adopted a participatory approach involving elementary school children and local residents across several stages, including a preliminary needs assessment, the provision of reading facilities, reading assistance sessions, and literacy-based activities such as shared reading, storytelling, and educational games centered on books. The findings demonstrated a noticeable increase in children’s engagement in reading activities, reflected in the growing number of visits and active participation in the literacy programs. Furthermore, the initiative strengthened community involvement in maintaining and sustaining literacy spaces within the village environment. The Sudut Baca Ceria serves as an alternative model of community-based literacy intervention that effectively promotes children’s reading interest and reinforces literacy culture in rural areas.